Ethanol Dry Reforming for H2-Rich Syngas Production Over Ce-Ni/Al2O3 Catalyst - Mahadi, Bahari; Abdullah, Bawadi; Alenazey, Feraih; Vo, Dai-Viet N. (2015)
The transformation of greenhouse gas, CO2 to fuels using heterogeneously catalytic processes has received significant attention due to the depleting petroleum resources, associated environmental problems and stringent environmental regulations. CO2 reforming of CH4 is considered as a suitable method for producing syngas to substitute petroleum-based energy. However, CH4 is an unrenewable resource and will probably be depleted next century. Thus, there is requirement of an alternatively sustainable and green approach for H2 synthesis. The production of H2 from ethanol dry reforming seems to be a promising method since it utilizes both bio-derived ethanol regarded as renewable resource and undesirable CO2 as feedstocks. However, the knowledge about CO2 reforming of ethanol is still limited. Hence, the aim of this research was to examine the physicochemical properties of 3%Ce-10%Ni/Al2O3 catalyst and study the influence of both reaction temperature and reactant partial pressure on activity and selectivity of CO2 reforming of ethanol. Co-impregnation method between Ce(NO3)3, Ni(NO3)2 precursor solutions and γ-Al2O3 support thermally pretreated at 973 K was used for synthesizing 3%Ce-10%Ni/Al2O3 catalyst. Ethanol dry reforming runs were carried out in a quartz fixed-bed reactor placed vertically in a split tubular furnace at reaction temperature range of 873 - 973 K under atmospheric pressure. Approximately 0.1 gcat of catalyst was sandwiched by quartz wool in the middle of the reactor. Gas hourly space velocity, GHSV= 42 L gcat-1 h-1 and mean particle size of 100-140 μm were used for all runs to ensure that the negligible internal and external transport resistances was present. The ratios of CO2 to C2H5OH were varied from 1:1 to 2.5:1 and vice versa. CO2 and C2H5OH mixture was diluted in N2 flow acting as a tie component for material balance purposes and ensuring the total flowrate of 70 ml min-1. 3%Ce-10%Ni/Al2O3 catalyst possesses high surface area of 138.56 m2 gcat-1 with pore volume and pore diameter of 0.23 cm3 gcat-1 and 59 nm, respectively. The BET area of catalyst was close to that of calcined γ-Al2O3 support suggesting the fine metal dispersion on support surface. In fact, the well dispersed metal on γ-Al2O3 surface was also captured by SEM analysis. The derivative weight profiles of temperature-programmed calcination revealed two characteristic peaks indicating the completely thermal decomposition of metal precursors and subsequent oxidation to metal oxides at below 600 K. The X-ray patterns of calcined Al2O3 support and 3%Ce-10%Ni/Al2O3 catalyst confirm that γ-Al2O3, NiO, CeO2 and NiAl2O4 phases were formed on catalyst surface during calcination. Both CO2 and C2H5OH conversions initially decreased with time-on-stream and appeared to be stable at ca. 4-5 h. A reduction in H2/CO ratio from 20 to 5 was observed with increasing reaction temperature from 873 K to 973 K probably due to the enhancement of reverse water-gas shift reaction. The consumption rate of C2H5OH and CO2 was improved with increasing partial pressure of CO2, PCO2. Interestingly, C2H5OH and CO2 conversions also enhanced with growing PC2H5OH and approached the maximum at around 30-35 kPa.